Literasi Pemanfaatan Home Industry Untuk Menunjang Pendapatan Masyarakat Desa - Kasnawati, Kasnawati; Demmanggasa , Yultan; Kusdiah, Yuli; Misbahuddin, Misbahuddin; Sriwati, Meny (ADPERTISI, 2023)
Community Service aims to provide knowledge and understanding to Village Communities for the Use of Home Industry to Support Village Community Income. Formulation of the problem faced is limited business capital and home industry marketing. The strategy carried out and recommended is to deliver material on mechanisms for cultivating the Village Community's mindset to manage the Village resources they own, such as in the Agriculture/Plantation, Tourism and Fisheries sectors, followed by discussions to find solutions that can be utilized. The conclusion drawn from this community service activity is that increasing literacy and knowledge about home industry runs smoothly to increase village community income and digital marketing